ANALISIS SEMIOTIK PEMANFAATAN PRACTICAL EFFECT PADA NARASI VISUAL FILM “OPPENHEIMER” (2023) - Nasution, Amaranila Nur Aqdin; Mutiaz, Intan Rizky (Cinelook: Journal of Film, Television, and New Media, 2024)
With the development of technology, the majority of widescreen movies are now produced utilizing computer assistance such as CGI. Even though biopics are based on true stories, many of them use computer-generated imagery (CGI) in their production. However, the increasing creativity of directors and the film industry, practical effects are still used to create more realistic scene atmosphere. Christopher Nolan is a famous director known for his distinctive use of practical effects in his films. The objective of this research is to analyse the correlation between the use of practical effects and their significance to the visual narrative in the film Oppenheimer (2023). This study involves observational research methods and is descriptive qualitative. The writer then selects visual representations of Oppenheimer's thought processes that utilize practical effect techniques. The author uses Ferdinand De Saussure's semiotic theory to identify the meanings of the practical effect shots used for visualization within Oppenheimer's mind in the film Oppenheimer (2023). The study's conclusion is that each scene's narrative in the film Oppenheimer (2023) holds significance that are related to the practical effects used to portray Oppenheimer's thought processes.